Security and Trust Management 6th International Workshop, STM 2010, Athens, Greece, September 23-24, 2010, Revised Selected Papers - Cuellar, Jorge; Lopez, Javier; Barthe, Gilles; Pretschner, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Workshop on Security and Trust Management, STM 2010, held in Athens, Greece, in September 2010. The 17 revised full papers presented were carefully reviewed and selected from 40 submissions. Focusing on high-quality original unpublished research, case studies, and implementation experiences, STM 2010 encouraged submissions discussing the application and deployment of security technologies in practice.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data encryption (Computer science).; Information Systems; Computer Science; Management of Computing and Information Systems; Data Encryption; Operating Systems; Computer Communication Networks; Computers and Society